Quantitative Analysis of the Influence of Temperature Factors on Total Phosphorus Content in Water - Wu, Manching (Transactions on Environment, Energy and Earth Sciences, 2024)
The purpose of this study is to systematically explore the influence of temperature factors on the total phosphorus content in water by quantitative analysis. In order to comprehensively reflect the water quality of different areas of the lake, the lake located in the suburbs was selected as the sampling point, covering the deep water area, shallow water area and coastal area. The sampling time is set as the representative dates of spring, summer, autumn and winter, and the laboratory control experiment is designed to determine the total phosphorus content in water under five temperature gradients of 5°C, 10°C, 15°C, 20°C and 25°C. Ammonium molybdate spectrophotometry was used to determine the total phosphorus to ensure the accuracy of the data. The experimental results show that with the increase of temperature, the total phosphorus content in water shows an increasing trend. At low temperature (5°C), the average total phosphorus content in each region is between 0.15 and 0.23 mg/L; However, when the temperature rises to 20°C and 25°C, the total phosphorus content increases significantly, reaching 0.30 and 0.35 mg/L respectively. The analysis of variance further confirmed that there were significant differences in the total phosphorus content under different temperature gradients (F=5.83, p=0.001), indicating that temperature was an important factor affecting the total phosphorus content in water. This study provides a scientific basis for understanding the influence of temperature on the total phosphorus content in water, and has important guiding significance for water quality monitoring and management.